New Brunswick: Let’s Not Waste a Crisis - Savoie, Donald J. (Journal of New Brunswick Studies / Revue d’études sur le Nouveau-Brunswick, 2010)
New Brunswick is staring at a crisis in the making. The crisis is economic in nature but, unless it is addressed with a sense of urgency, it may well make New Brunswick increasingly difficult to govern. The province is confronting a host of economic challenges: a structural deficit, an aging population, uncertainty surrounding federal transfers, sluggish economic growth, a highly competitive global economy, and an inability to attract new Canadians. The paper argues that New Brunswick should not waste a crisis and consider doing things that it "could not do before." The paper maintains that the province’s academic community has an important role to play in ensuring that New Brunswick does not waste the looming crisis.